The Influence of Co-Curricular Learning on Cadets' Skills in the Construction and Stability of Ships Course at Malahayati Maritime Polytechnic - Hermanto, Fazri; Kurniadi, Dedy (Green Publisher Indonesia, 2023)
To achieve the goals of national education, efforts are needed, such as maximizing the learning experiences of students because learning experiences greatly influence learning outcomes, especially in vocational education. Students' learning experiences can be accommodated through three activities: curricular, extracurricular, and co-curricular. While curricular and extracurricular activities are frequently heard of and discussed, it seems that co-curricular activities have not been fully utilized for strengthening learning. Co-curricular activities are carried out to reinforce, deepen, or enrich curricular activities. They are conducted outside regular class hours (including during breaks) and can take place in school or off-campus to support curricular implementation. Co-curricular activities must directly support the curricular activities and the students' learning interests with an emphasis on a more realistic context. Therefore, it is not solely focused on the curricular content, as it emphasizes real-world problem contexts, co-curricular activities have numerous benefits for students. Some of the benefits of co-curricular activities include character development, the cultivation of good values, the development of social skills and leadership abilities, the promotion of awareness and appreciation of diversity, increased enthusiasm in addressing evolving global issues, and the development of literacy and numeracy competencies. This can also be observed at Malahayati School of Maritime Polytechnic where co-curricular learning is one of the mandatory activities applied to cadets to help reinforce the learning materials they acquire in the classroom.